PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MELALUI METODE DISCOVERY DENGAN MENGGUNAKAN MEDIA GAMBAR MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA TA 2011/2012 UNIVERSITAS EKASAKTI PADANG - Yossy Idris; Harris Efendi Thahar; Novia Juita (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: This research is aim to describe improving students writing skill through discovery learning methods by using images at Prodi Indonesian an Literature Education academic year 2011/2012 of Ekassakti University Padang. This study is Classroom Action Research. The subject of this research was conducted by the two cycles. Each cycle was done in the different strages of learning. They are : 1. Planning, 2. Action, 3. Observation, 4. Reflection. The instrumentation are : a. Performance test, b. Observation and c. Observation note. The result of this research shows/describe this method by using images in teaching and learning process improve the student writing skill at Eka Sakti University academic year 2011/2012. The students writing skill improve significantly. The students response in apllying discovery method by using images were better as well as the improving their writing skill in descriptive text. Based on the performance test, the students writing skill in descriptive is about 60,27 % in the pre-cycle. After the students were given the action in the first cycle, that skill increased become 72 % and the for second cycle increased become 79%. Key word :writing, description, discovery method, images media, classroom action research.